The use of NAAT- PCR to determine asymptomatic chlamydia and gonorrhoea infections in infertile patients undergoing hysterosalpingogram at the federal medical centre, Yenagoa, South-South Nigeria - Oriji, Chibuzor P.; Kiridi, Kelvin E.; Allagoa, Dennis O.; Omietimi, James E.; Orisabinone, Idowu B.; Makinde, Olakunle I.; Njoku, Chidiebere (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The roles of Chlamydia trachomatis and Neisseria gonorrhoeae in the aetiology of infertility due to tubal occlusion have been established by various studies. These organisms may lead to pelvic infection by ascending into the upper genital tract through any instrumentation like hysterosalpingography. The objectives were to determine the prevalence of asymptomatic chlamydial and gonorrhoeal infections of the genital tract among women being investigated for infertility referred for hysterosalpingography; the relationship of these infections with tubal pathologies; and if routine endo-cervical screening and prophylactic antibiotics be recommended for these patients. Methods: This was a descriptive cross-sectional study. The study population consisted of consecutive 220 infertile women that met the inclusion criteria for this study. Consent was obtained. Endo-cervical swab was taken for NAAT-PCR for Chlamydia trachomatis and Neisseria gonorrhoeae. Hysterosalpingography was carried out. Data was analyzed using SPSS (version 22). Results: Amongst the 220 women, 9 (4.1%) had asymptomatic chlamydia infection. None had gonorrhoea infection and 211 (95.9%) had none of these two organisms. Forty-eight (21.9%) of the 220 women had bilateral tubal blockage and 9 (18.8%) out of these 48 women had asymptomatic infection with Chlamydia trachomatis. Conclusions: There is a statistically significant association between tubal blockage and chlamydia infection (p = 0.00) [RR 4.31 (3.37-5.50)]. There was no evidence to recommend routine screening/antibiotics considering the low prevalence of microbes and the absence of post-HSG pelvic infection. Results from a multicenter randomized controlled trial will be more representative.